DETERMINATION OF CHANGES IN FIELD AREA WITH FOOD-SUPPORTING CAPACITY USING REMOTE SENSING IN AGAM - Syukra Alhamda; Yudi Antomi (International Remote Sensing Applied Journal, 2022)
West Sumatra Province is one of the provinces in Indonesia which is the best rice producer in Indonesia, but a large number of conversions to paddy fields has resulted in food threats for the local population, data from the Ministry of Agriculture states that the decline in paddy fields in West Sumatra in 2008 was 228,176 ha. , in 2009 amounted to 229,693 ha, then in 2010 amounted to 231,463 ha, and in 2011 amounted to 229,368 ha, then decreased in 2012 amounted to 224,182 ha and in the area of West Sumatra Cities that experienced land conversion, namely Agam Regency, conversion of agricultural land to non-use Agriculture is a threat to national food security.